Diagnostic Accuracy of HRCT Temporal Bone in Evaluation of Cholesteatoma, Taking Histopathology as Gold Standard - Saeed, Maryam; Pasha, Nazahat (Biological and Clinical Sciences Research Journal, 2025)
Cholesteatoma is a destructive lesion of the temporal bone that may lead to significant complications if left untreated. High-resolution computed tomography (HRCT) plays a pivotal role in its preoperative evaluation due to its superior spatial resolution. However, histopathology remains the gold standard for diagnosis. Objective: To assess the diagnostic accuracy of HRCT temporal bone in detecting cholesteatoma, using histopathological findings as the reference standard. Methods: This cross-sectional diagnostic accuracy study was conducted over six months (May–October 2024) at the Department of Diagnostic Radiology, CPEIC Multan. A total of 147 patients aged 2–60 years with clinical suspicion of cholesteatoma were included through non-probability consecutive sampling. All patients underwent HRCT followed by surgical exploration and histopathological evaluation. Diagnostic accuracy metrics, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy of HRCT, were calculated using 2x2 contingency tables. Stratified analyses were performed by age, gender, symptom duration, and laterality. Results: Of the 147 patients, 92 (62.6%) were confirmed to have cholesteatoma on histopathology, while 88 (59.9%) were diagnosed via HRCT. HRCT demonstrated a sensitivity of 90.2%, specificity of 90.9%, PPV of 94.3%, NPV of 84.7%, and an overall diagnostic accuracy of 90.1%. The highest diagnostic performance was observed in the 21–40 years age group. Diagnostic accuracy remained consistent across gender and laterality, with slightly higher accuracy noted for patients with symptom duration of 6–12 months. Conclusion: HRCT temporal bone is a highly accurate and reliable imaging modality for diagnosing cholesteatoma and provides valuable preoperative information. However, given its limitations in detecting small or atypical lesions, histopathological confirmation remains essential. Incorporating multimodal imaging, including DWI MRI, may further enhance diagnostic precision, particularly in complex cases or recurrence surveillance.